Advancing emergency care: A 20-year bibliometric analysis of prehospital airway suction research - Ardian Jafar A. Hukum; Sidik Awaludin (Jurnal Keperawatan Padjadjaran, 2025)
Background: Prehospital airway suction is a critical intervention for maintaining airway patency in emergencies, especially in trauma, cardiac arrest, or airway obstruction. Despite its clinical significance, research on its effectiveness, device innovation, and procedural outcomes remains underrepresented compared to other airway management practices. Purpose: This study systematically maps the scientific landscape, research trends, and thematic structures of prehospital airway suction, identifying clusters, gaps, and future directions. Methods: A bibliometric analysis was conducted using Publish or Perish to retrieve articles from Scopus and PubMed (2005–2025) with the keyword “prehospital airway suction.” Data were analysed using VOSviewer for co-occurrence of terms in titles and abstracts, producing network, overlay, and density visualisations. Results: From 90 relevant publications, 71 (78.89%) directly addressed prehospital airway suction. Five thematic clusters emerged: (1) airway devices and preparation, (2) healthcare providers and prehospital procedures, (3) suction effectiveness and safety, (4) advanced techniques such as Suction-Assisted Laryngoscopy and Airway Decontamination (SALAD), and (5) clinical outcomes and evaluations. Overlay visualisation revealed a recent research shift (2020–2025) toward portable device innovation, advanced suction methods, and simulation-based training. The most cited work was Prekker et al. (2014), cited 79 times. Conclusion: This first bibliometric study on prehospital airway suction highlights priorities in procedural standardisation, portable and efficient device development, effective suction techniques, and enhanced simulation-based training. The findings offer a reference for future research targeting specific populations, extreme emergencies, and the integration of emerging technologies.